Visualization of plant cell wall lignification using fluorescence‐tagged monolignols. (23rd August 2013) - Tobimatsu, Yuki; Wagner, Armin; Donaldson, Lloyd; Mitra, Prajakta; Niculaes, Claudiu; Dima, Oana; Kim, Jeong Im; Anderson, Nickolas; Loque, Dominique; Boerjan, Wout; Chapple, Clint; Ralph, John
Summary Lignin is an abundant phenylpropanoid polymer produced by the oxidative polymerization of p‐hydroxycinnamyl alcohols (monolignols). Lignification, i.e., deposition of lignin, is a defining feature of secondary cell wall formation in vascular plants, and provides an important mechanism for their disease resistance; however, many aspects of the cell wall lignification process remain unclear partly because of a lack of suitable imaging methods to monitor the process in vivo. In this study, a set of monolignol analogs γ‐linked to fluorogenic aminocoumarin and nitrobenzofuran dyes were synthesized and tested as imaging probes to visualize the cell wall lignification process in Arabidopsis thaliana and Pinus radiata under various feeding regimens. In particular, we demonstrate that the fluorescence‐tagged monolignol analogs can penetrate into live plant tissues and cells, and appear to be metabolically incorporated into lignifying cell walls in a highly specific manner. The localization of the fluorogenic lignins synthesized during the feeding period can be readily visualized by fluorescence microscopy and is distinguishable from the other wall components such as polysaccharides as well as the pre‐existing lignin that was deposited earlier in development.